Embryos refrozen-thawed by vitrification lead to live births: Case report - Mauri, Ana L.; Petersen, Claudia G.; Oliveira, João B.A. [UNESP]; Baruffi, Ricardo L.R.; Al-Hasani, Saffa; Franco Junior, Jose Gonçalves [UNESP] (Springer Nature, 2011)
Objective: To describe two successful cases of utilizing refrozen blastocysts by vitrification derived from supernumerary embryos. Design: Case report. Setting: Private fertility clinic. Subjects: Two infertility couple. Interventions: Refrozen blastocysts by vitrification derived from supernumerary embryos. Main outcome measures: Obstetric and pediatric results. Results: Two pregnancies obtained from refrozen-warmed blastocysts led to two healthy babies being born without clinical or genetic problems. Conclusion: These case reports support the notion of safely repeating cryopreservation. However, despite these favorable results, there is still a need for prospective controlled studies on the obstetric and neonatal repercussions of refreezing and of vitrification in particular. © 2010 Middle East Fertility Society.
Keywords: Cryopreservation; Frozen embryo transfer; Refrozen embryos; Vitrification; adult; blastocyst; case report; cell cycle phase; cell viability; clinical protocol; cryopreservation; density gradient centrifugation; embryo culture; embryo transfer; female; female infertility; fertilization in vitro; freeze thawing; human; intermethod comparison; live birth; medical history; phase transition; pregnancy outcome; repeat procedure; vitrification